Pengaruh Motivasi Kerja terhadap Etos Kerja dengan Etika Tanggung Jawab sebagai Variabel Intervening pada Pegawai BPSDM Provinsi Jambi - Sinta Helza Natali; Dwi Kurniawan; Fitri Widiastuti (Pusat Riset dan Inovasi Nasional, 2026)
The purpose of this study was to determine the direct influence of work motivation on work ethic and ethical responsibility, the influence of ethical responsibility on work ethic, and the indirect influence of work motivation on work ethic through ethical responsibility as an intervening variable on employees at the Human Resources Development Agency of Jambi Province. The method used was quantitative research. The results of the study showed that work motivation towards work ethic had a significance value of 0.000 (P <0.05), work motivation towards ethical responsibility had a significance value of 0.000 (P <0.05), and ethical responsibility towards work ethic had a significance value of 0.000 (P <0.05). Furthermore, the indirect effect of work motivation on work ethic through the ethics of responsibility has a significance value of 0.000 (P <0.05), so that work motivation influences work ethic through the ethics of responsibility as an intervening variable. In conclusion, work motivation influences work ethic through the ethics of responsibility as an intervening variable for employees at the Human Resources Development Agency of Jambi Province.